Aberrant interaction of calmodulin with the ryanodine receptor develops hypertrophy in the neonatal cardiomyocyte - Gangopadhyay, Jaya P. (2011)
We have recently shown that the inter-domain interaction between the two domains of ryanodine receptor (RyR), calmodulin binding domain (CaMBD) and CaM-like domain (CaMLD), activates the Ca(2+) channel, and this process is called ‘formation of activation-link’ [Gangopadhyay, J. P. and Ikemoto, N. (2008) Biochem. J. 411 415–423]. Thus, CaM that is bound to the CaMBD is expected to interfere the activation-link formation, thereby stabilizing the closed state of channel under normal conditions. Here we report that upon stimulation of neonatal cardiomyocytes with pro-hypertrophy agonist endothelin-1 (ET-1), CaM dissociates from the RyR, which induces a series of intracellular events: increased frequency of Ca(2+) transients, translocation of the signaling molecules CaM, CaM kinase II (CaMKII) and the transcription factor N-FAT (nuclear factor of activated T-cell) to the nucleus; then these events lead to the development of hypertrophy. Importantly anti-CaMBD antibody that interferes with the activation-link formation prevented all of these intracellular events that would have been triggered by ET-1, and then prevented the development of hypertrophy. These results indicate that the aberrant formation of the activation-link between CaMBD and CaMLD of RyR is a key step in the development of hypertrophy in cultured cardiomyocytes.